Technology Fatigue: The Art of Balanced Learning through Project Based Learning in Christian School - Hermawati, Oki; Ariesta, Eliza; Julisar, Julisar; Hananuraga, Rahula (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Technology has an important role in advancing the world of education, specifically in learning. The Covid 19 pandemic that hit the world and in the Indonesian context has changed the face of learning from traditional to blended learning and hybrid learning where technology is the main vehicle. After the Covid 19 pandemic, a learning model that was closely related to the use of technology was formed for teachers and students. Fatigue in using technology is starting to be felt by teachers and students with a survey at a Christian school in Jakarta and West Java which shows reduced student interest in using various kinds of learning applications and reduced teacher interest in using learning platforms. This technology fatigue problem requires a balanced solution in the use of technology as a tool in learning to achieve an effective and more advanced learning due to the use of appropriate and balanced technology in learning at school through Project-Based Learning.